Compensation and Motivation as Determinant Bases of Employee Work Productivity - Setyarto, Dwiatmodjo Budi; Syauqi, Ahmad; Octoviani, Aniza; Pebrianto; Awaludin, Dipa Teruna (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The purpose of this research was to analyze and examine factors that may influence employee work productivity at CV Klaten Energy. These factors include compensation and motivation. This research employed a quantitative method with regression analysis. Data were collected using an online questionnaire distributed to CV Klaten Energy production employees. The research population consisted of 58 CV Klaten Energy production employees. The sample was saturated/census sampling. Data were analyzed using IBM SPSS version 26 and subjected to several tests, including validity, reliability, classical assumption testing, multiple linear regression analysis, and the coefficient of determination test. The results of this research indicate that compensation and motivation significantly influence employee productivity at CV Klaten Energy. Higher compensation and motivation provided by leaders can increase work productivity.